A study of the distance teacher education programme (DTEP) offered by the Lesotho College of Education in Maseru Lesotho. - Chaka, Claurinah Malemohang (My University, 2012)
The study set out to assess the quality of the DTEP offered by the LCE by examining its strengths and limitations regarding student teachers‟ home and academic background, mode of delivery, entry requirements, course materials, content and pedagogic approach. This was done through analysis of some course documents and materials, interviewing course designers, tutors as well as final year student teachers. DTEP appears to be doing well in some areas and not so well in others. To start with, the programme came as the main answer to qualifying the teachers that were employed as un/under qualified at the pressing demands of UPE and FPE in the early 2000s. DTEP goes beyond teaching primary school content and methodology, onto teaching content aimed at opening doors for further study and thus other careers for its clientele. But there‟s still dire need to convince student teachers that this is good practice and for their benefit and not an unnecessary burden, as they perceive it to be. DTEP also appears to be succeeding in not just changing the negative attitudes and/or perceptions that most of its clientele tend to have at entry point, but also in them actually changing from wrong practices as well. However, the programme is characterized with some serious administrative challenges such as lack of transport which results in late delivery of study materials and irregular school visits. Also the DTEP entry qualifications are very low and yet there‟s no form of bridging course put in place to compensate for this. It as well seems that, though they are the only means of course communication, the DTEP course materials tend to be well written, interactive and thus of a good quality. The revisions of such materials, started late 2009, was completed early 2010. DTEP tutors as well stress to their students the importance of learner centred methods of teaching even though they are not able to demonstrate their use to them most of the time.
Keywords: Teacher education; Lesotho College of Education; Distance teacher education programme